The Impact of Instructional Leadership, Organizational Culture, and Job Satisfaction on Teacher Commitment in Primary Schools - Sucitra, Diah Ayu; Hariri, Hasan; Riswandi, Riswandi; Handoko, Handoko (Universitas Islam Negeri Raden Intan Lampung, 2024)
The purpose of this study was to examine the effect of principals' instructional leadership and organizational culture on organizational commitment through job satisfaction. This research employed a quantitative approach. The population of this study comprised all primary school teachers in Pringsewu Regency, totaling 2,736 teachers. From this population, a sample of 350 teachers was selected using the cluster random sampling technique. Data collection was conducted by distributing questionnaires using a five-point Likert scale. The data analysis technique used in this study was path analysis. The results showed that the direct effect of instructional leadership on job satisfaction was 32.2%. The direct effect of job satisfaction on organizational commitment was 17.6%. The direct effect of instructional leadership on organizational commitment was 30.6%. Furthermore, the indirect effect of instructional leadership on organizational commitment through job satisfaction was 2%, with the remaining influence attributed to other variables. Based on the study's results, several recommendations are provided, emphasizing that the principal's instructional leadership significantly contributes to organizational commitment. It is recommended that relevant parties focus on improving the principal recruitment system and providing training to principals to enhance their leadership capabilities.